A pilot study on the application of waste utilization value on waste generated by five garment manufacturers - Semitara, Earl Rico
The Waste Utilization Value, an original concept developed as a guide for evaluating the economic value of wastes, is the value of a waste in monetary units per unit measure. Wastes that could turn into profit have positive WUVs while pollutant or hazardous wastes have negative WUVs. This study proposes to apply the proposed model by Jose and Tio on wastes generated by five garment manufacturers. The WUV is dependent on the six quantifiable factors namely separability, handling, technological, demand, cost and profit factors. There are 15 solid positive wastes identified from these data where the WUV was expressed in terms of price ranges rather than exact values. The model correctly classified 12 of the 15 types of wastes into predicted price ranges. The statistical analysis also showed that of the six variables considered in the discriminant function, the top two variables that consistently contribute substantially to the group separation are the technological and separation factor. The result of this study supports the current priority on the improvement of technology in waste utilization and recycling especially on the wastes generated by the garment industry. The findings on the new classifications of the 3 misclassified wastes shall also serve as a "yardstick" to manufacturers for better profitability of waste utilization.